THE Strategy Implementation of Programs of Nahdlatul Ulama Regional Board (PWNU) West Java Province in Serving the Umat - dasuki, dasuki; Rohendi, Acep; Andriani, Rian (Pergunu Jawa Barat, 2025)
Nahdlatul Ulama as an organization based on traditional society and pesantren that adheres to the ideology of Ahlus Sunnah wal Jama'ah aims to help to create a just society, welfare of the people and public good. Therefore, to realize Nahdlatul Ulama's goals, its movement then covers several areas of community services including religious, social, educational, economic and other fields. The aim of this research is to find out and analyze how strategy implementation of programs from the Regional Board of Nahdlatul Ulama (PWNU) West Java Province is implemented in optimizing its services to the people. The method used in this research is qualitative. In this research, the research subjects were the Organization Board of PWNU, both from the Syuriyah and Tanfidziyah, the Board of Lembaga and Banom and jama'ah related to the implementation of community service programs. Based on the research results, it shows that the implementation strategy of the work programs carried out by the Board of PWNU has experienced relatively a lot of progress, including in terms of organizational management, however, it still faces challenges in efforts to modernize its organizational governance in a more professional manner. So, some optimizations are needed to improve organizational governance in the future so that various community service programs can be maximized.